Delineation of the population genetic structure of Culicoides imicola in East and South Africa. Issue 1 (December 2015) - Onyango, Maria; Michuki, George; Ogugo, Moses; Venter, Gert; Miranda, Miguel; Elissa, Nohal; Djikeng, Appolinaire; Kemp, Steve; Walker, Peter; Duchemin, Jean-Bernard
Abstract Background Culicoides imicola Kieffer, 1913 is the main vector of bluetongue virus (BTV) and African horse sickness virus (AHSV) in Sub-Saharan Africa. Understanding the population genetic structure of this midge and the nature of barriers to gene flow will lead to a deeper understanding of bluetongue epidemiology and more effective vector control in this region. Methods A panel of 12 DNA microsatellite markers isolatedde novo and mitochondrial DNA were utilized in a study ofC. imicola populations from Africa and an outlier population from the Balearic Islands. The DNA microsatellite markers and mitochondrial DNA were also used to examine a population of closely relatedC. bolitinos Meiswinkel midges. Results The microsatellite data suggest gene flow between Kenya and south-west Indian Ocean Islands exist while a restricted gene flow between Kenya and South AfricaC. imicola populations occurs. Genetic distance correlated with geographic distance by Mantel test. The mitochondrial DNA analysis results imply that theC. imicola populations from Kenya and south-west Indian Ocean Islands (Madagascar and Mauritius) shared haplotypes whileC. imicola population from South Africa possessed private haplotypes and the highest nucleotide diversity among the African populations. The Bayesian skyline plot suggested a population growth. Conclusions The gene flow demonstrated by this study indicates a potential risk of introduction of new BTV serotypes by wind-borne infectedCulicoides into the Islands. Genetic similarity between Mauritius and South Africa may be due to translocation as a result of human-induced activities; this could impact negatively on the livestock industry. The microsatellite markers isolated in this study may be utilised to studyC. bolitinos, an important vector of BTV and AHSV in Africa and identify sources of future incursions.